Raw and processed microscope images of fixed cells at baseline and following various experimental perturbations - McClatchey, P. Mason (Data Brief, 2016)
The data included in this article comprise raw and processed images of fixed cells at baseline and subjected to various experimental perturbations. This dataset includes images of HUVEC cells fixed and subsequently incubated at either 37 °C or room temperature, primary rat vascular smooth muscle cells exposed to 25 mM glucose, and SH-SY5Y neurons exposed to hydrogen peroxide. Raw images appear exactly as they were captured on the microscope, while processed images show the binarization provided by software used for measurements of mitochondrial morphology. For in-depth discussion of the experiments and computational methods pertaining to this data, please refer to the corresponding research article titled “Fully automated software for quantitative measurements of mitochondrial morphology” (McClatchey et al., in press) [1].